Rapid detection of bacterial infection using a novel single-tube, four-colour flow cytometric method: Comparison with PCT and CRP - Jari Nuutila (Elsevier, 2021)
ABSTRACT: Background: A key factor behind the unnecessary use of antibiotics is the lack of rapid and accurate diagnostic tests. In this study, we developed a novel and fast flow cytometric single-tube method to detect bacterial infections within 30 minutes. Methods: Quantitative flow cytometric four-colour analysis of host biomarkers CD35, CD64, CD329, and MHC class I expression on neutrophils and lymphocytes was performed on samples taken from 841 febrile patients with suspected infection. Obtained data was incorporated into the four-colour bacterial infection (FCBI)-index, using the developed bacterial infection algorithm. Findings: In distinguishing between microbiologically confirmed bacterial (n = 193) and viral (n = 291) infections, the FCBI-index method was superior to serum C-reactive protein (CRP) and procalcitonin (PCT). In 269 confirmed viral respiratory tract infections, 43% (95% CI: 37–49%) of the patients had an increased FCBI-index, suggesting probable bacterial coinfection. Interpretation: The proposed FCBI-index test might be a potent additional tool when assessing appropriateness of empiric antibiotic treatment. Funding: This study has been financially supported by Turku University Hospital (Turku, Finland) and The Finnish Medical Foundation.